Nanoglasses: a new kind of noncrystalline materials - Gleiter, Herbert (Beilstein Journal of Nanotechnology, 2013)
Nanoglasses are a new class of noncrystalline solids. They differ from today’s glasses due to their microstructure that resembles the microstructure of polycrystals. They consist of regions with a melt-quenched glassy structure connected by interfacial regions, the structure of which is characterized (in comparison to the corresponding melt-quenched glass) by (1) a reduced (up to about 10%) density, (2) a reduced (up to about 20%) number of nearest-neighbor atoms and (3) a different electronic structure. Due to their new kind of atomic and electronic structure, the properties of nanoglasses may be modified by (1) controlling the size of the glassy regions (i.e., the volume fraction of the interfacial regions) and/or (2) by varying their chemical composition. Nanoglasses exhibit new properties, e.g., a Fe90Sc10 nanoglass is (at 300 K) a strong ferromagnet whereas the corresponding melt-quenched glass is paramagnetic. Moreover, nanoglasses were noted to be more ductile, more biocompatible, and catalytically more active than the corresponding melt-quenched glasses. Hence, this new class of noncrystalline materials may open the way to technologies utilizing the new properties.
Keywords: amorphous materials; ferromagnetism; nanoglasses; nanostructured materials; noncrystalline materials